Kecenderungan Open-Mindedness di PTAI dalam Perspektif Stakeholder Kampus STAIN Jember: The Tendency of Open-Mindedness in Islamic Higher Education Institutions (PTAI) from the Perspective of Stakeholders at the State Islamic College of Jember (STAIN Jember) - Dyah Nawangsari (Fenomena, 2009)
This study addresses the crucial issue of Indonesian Islamic Higher Education (PTAI) navigating between academic expectations and social expectations amidst globalization, often facing public controversy when producing non-mainstream religious thoughts. The broader problem lies in the dilemmatic position of PTAI as both an academic and a da'wah institution, struggling with scientific approaches to sacred subjects. This research aims to understand the tendency of open-mindedness at PTAI from the perspective of STAIN Jember stakeholders. Employing a qualitative phenomenological design, the study conducted in-depth interviews, participant observation, and documentation with key informants including lecturers of religious and secular subjects, as well as students. The findings reveal that students primarily entered PTAI expecting deepened religious understanding, resulting in initial confusion when exposed to rational-scientific approaches, yet ultimately leading to distinctive personal religious stances without regret or apostasy. Lecturers generally accept open-mindedness as necessary for Islam's relevance, with differing boundaries based on their academic disciplines—religious subject lecturers tend to adhere to classical methodologies, while those teaching profane subjects are more receptive to Western methods. The study concludes that open-mindedness tendencies at PTAI are accepted as a necessity, with variations in its limits, and recommends that such intellectual freedom be maintained within mainstream Islamic corridors to foster constructive academic dialogue. Penelitian ini membahas isu krusial tentang Pendidikan Tinggi Agama Islam (PTAI) yang berada di antara harapan akademis dan harapan sosial di tengah globalisasi, seringkali menghadapi kontroversi publik ketika melahirkan pemikiran keagamaan non-mainstream. Peta masalah yang lebih luas terletak pada posisi dilematis PTAI sebagai lembaga akademis sekaligus dakwah, yang bergulat dengan pendekatan ilmiah terhadap subjek sakral. Penelitian ini bertujuan memahami kecenderungan open-mindedness di PTAI dari perspektif stakeholder STAIN Jember. Dengan pendekatan kualitatif fenomenologis, penelitian dilakukan melalui wawancara mendalam, observasi partisipan, dan dokumentasi terhadap informan kunci yang terdiri dari dosen mata kuliah agama dan profan serta mahasiswa. Temuan penelitian menunjukkan bahwa mahasiswa memasuki PTAI dengan harapan mendalami agama, mengalami kebingungan awal saat dihadapkan pada pendekatan rasional-ilmiah, namun akhirnya mencapai sikap keberagamaan khas pribadi tanpa penyesalan atau kemurtadan. Para dosen umumnya menerima open-mindedness sebagai keniscayaan agar Islam relevan, dengan batasan berbeda berdasarkan bidang keahlian—dosen ilmu agama cenderung berpegang pada metodologi klasik, sementara dosen ilmu profan lebih terbuka terhadap metode Barat. Penelitian menyimpulkan bahwa kecenderungan open-mindedness di PTAI diterima sebagai keniscayaan dengan variasi batasannya, dan merekomendasikan agar kebebasan intelektual tetap berada dalam koridor pemahaman agama mainstream untuk membangun dialog akademis yang konstruktif.